Developing an understanding procedures observation rubric for mathematics intervention teachers. (4th March 2020) - Crawford, Angela R.; Johnson, Evelyn S.; Zheng, Yuzhu Z.; Moylan, Laura A.
Abstract: This study describes the initial psychometric evaluation of an Understanding Procedures observation rubric. The instrument is intended to provide feedback to teachers working in mathematics intervention settings. The rubric translates the research base from mathematics education and special education into practice in the form of specific items and descriptors of performance levels. A sample of 16 intervention teachers across three states provided three videos each of their instruction of students in mathematics intervention classes. Ten external raters evaluated the videos. We analyze the ratings using many‐facet Rasch measurement. Analyses of the teacher, item, rater, and lesson facets show good psychometric quality for the instrument. Implications for research and professional development are discussed.